Analisis Misregister Cetak Brosur Pada Mesin Ofset Heidelberg GTO 2 Warna: (Studi kasus: Uji Kompetensi Siswa Kelompok 9 SMK Grafika Di Mardi Yuana Bogor 2022) - Galingging, Rumbel; N.M Sitompul, Toni; Pandita, Rahma (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Media Komunikasi Trisakti, 2023)
This study aims to determine the results of the print brochure by students during the Competency Test at SMK GraÏ”ika Mardi Yuana Bogor. The offset print system is very dominating for the amount of printed with moderate to small quantity, in the printing process requires skills and techniques in the printing process. Many problems that often arise from paper material and printing techniques, efforts to control the print problem of Misegister on the Heidelberg GTO 2 color of the paper are derived from non -elbow paper, the anleg adjustment is not precise and from the engine factor because the engine is not maintained, the machine is old and due to the number of molds a little so that the operator ignores the data printing process procedure taken from the Pareto analysis tool in the printing process. From the factors causing problems in the printing process of 4 colors in the Heidelberg GTO 2 color offset, it is due to the incorrect plate installation problem so that the print register is difÏ”icult to achieve and often changes. How to control the print in the brochure printing process by changing the clamping clamping clamp and mastered printing theory and following print operational standards.